THE ROLE OF DIET AND MICRONUTRIENTS IN MIGRAINE PREVENTION - Patrycja Świercz; Konrad Strużek; Agnieszka Kwiatkowska; Ewelina Mączka; Wiktor Tracz; Kinga Teper; Sandra Khiralla-Gawlik; Aleksandra Anna Strzelecka; Aleksandra Ewa Basak; Jakub Tomaszewski (International Journal of Innovative Technologies in Social Science, 2025)
Migraine is a chronic neurological disorder characterized by recurrent episodes of throbbing headache, often unilateral, accompanied by symptoms such as nausea, photophobia, and phonophobia. Dietary factors and deficiencies in micronutrients, such as magnesium, riboflavin, coenzyme Q10, vitamin D, and omega-3 fatty acids, play a significant role in modulating the frequency and severity of migraine attacks.This article analyzes the biological mechanisms linking diet to migraine, the effectiveness of supplementation with selected micronutrients, and the importance of eliminating potential trigger factors, such as tyramine, monosodium glutamate, or aspartame.Based on a review of scientific literature, including Polish and English-language sources, it was demonstrated that a properly balanced diet, including the Mediterranean and ketogenic diets, and individually tailored supplementation can significantly reduce the risk of migraine attacks. The need for further research to optimize dietary strategies and personalize interventions to improve the quality of life of migraine patients was emphasized.